Plan estratégico para la Avícola Mia de la ciudad de Calceta - Briones Bravo, Khaterin Nicole (2023)
The research was carried out with the objective of designing a strategic plan to strengthen business management in the MIA poultry farm, for which three phases were developed: (1) the internal and external environment of the poultry farm was diagnosed using the application as input from an interview with the general manager, the secretary and the productive director of the poultry farm, in addition to PESTEL analysis, with which the internal and external factors of the company were identified and prioritized through a prioritization matrix, which were evaluated by employees the matrix EFI and EFE; (2) the strategic direction of the poultry farm was formulated, defining the mission, vision, strategic and financial objectives, corporate values and institutional policies, in addition, the strategies were designed using the Crossed SWOT matrix, the strategic position was valued with the PEYEA matrix and the strategic map was prepared to illustrate the proposed direction; (3) a Balanced Scorecard was developed that expanded the definition of indicators, the measurement of which is proposed in accordance with the indicator traffic light technique. The results obtained indicate that the poultry industry has a weak internal position because business management does not comply with the appropriate processes, however, it has strengths and opportunities that facilitate its growth and development in the market. It is concluded that the proposed strategic planning contributes to organizational success, since it includes guidelines for economic growth, product and process development, staff training, and customer relations.